Songs for dead children - Blodgett, E. D. (Robert Kroetsch series., 2018)
In a series of poems inspired by Gustav Mahler's Kindertotenlieder, E.D. Blodgett searches for meaning amidst grief. In the contemplative gentleness of his words, he finds the special light children possess in their state of unknowing as they encounter the world. These sparse poems move through acceptance and resignation to the solace that exists in the word. Blodgett's poetry will speak to readers who have experienced loss, are exploring grief, or want to find a way to connect with stillness. as bells that ring through the winter air the clear laughter of children sings in the trees almost like brooks bursting in spring the air stands up its joy unbound the breath of it the bright birth of stars.